Perception of a Perpetrator as a Successful Person Predicts Decreased Moral Judgment of a Rape Case and Labeling it as Rape - Nyúl, Boglárka; Kende, Anna; Engyel, Márton; Szabó, Mónika (Frontiers in Psychology, 2018)
Rape cases of celebrities and other influential figures have caught the public eye in recent years. Following the media attention to these cases, people made strong judgements either believing or doubting the victims. Even though some of these men were convicted, they tended to receive little jail time and continued to enjoy people’s sympathy, as in the case of the Hungarian national swimming-coach. We examined whether opinions about the coach’s rape were affected by rape myth acceptance and the perception of the perpetrator as a successful person. We conducted two online surveys to reveal this connection at two different points. The case was still somewhat ambiguous at the time of data collection for Study 1 (N = 870) because the perpetrator denied it. However, Study 2 (N = 105) took place after the perpetrator admitted his crime. In line with our predictions, we found that in the uncertain context of Study 1, rape myth acceptance and the perception of the perpetrator as a successful person predicted whether respondents labelled the incident as rape, and how the perpetrator’s reactions were judged morally. In the certain condition of Study 2, rape myth acceptance continued to predict moral judgements, but it no longer predicted whether the incident was labelled as rape. These findings showed that in the evaluation of a rape case of a popular and powerful person, perception of the perpetrator’s success can affect the overall evaluation of the case based on the level of rape myth acceptance. However, such a connection is more pronounced when there are still ambiguities regarding the rape. We therefore suggest that both rape myth acceptance and the effect of the overall perception of the perpetrator are considered in rape prevention programs, because rape cases rarely appear as certain and unambiguous in the media.